2020
DOI: 10.1073/pnas.2008540117
|View full text |Cite
|
Sign up to set email alerts
|

One gene, multiple ecological strategies: A biofilm regulator is a capacitor for sustainable diversity

Abstract: Many bacteria cycle between sessile and motile forms in which they must sense and respond to internal and external signals to coordinate appropriate physiology. Maintaining fitness requires genetic networks that have been honed in variable environments to integrate these signals. The identity of the major regulators and how their control mechanisms evolved remain largely unknown in most organisms. During four different evolution experiments with the opportunist betaproteobacterium Burkholderia cenocepacia in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 58 publications
3
10
0
Order By: Relevance
“…2A , cepacian production was significantly reduced in the single mutants Δ bceC and Δ gtaB and completely abolished in the Δ bceC Δ gtaB double mutant, indicating that both cepacian clusters bce-I and bce-II are required for high-level cepacian production. Inactivation of rpfR had no apparent effect on cepacian production, suggesting that RpfR is not involved in the regulation of this EPS molecule, in agreement with a recent transcriptome analysis 21 . Phenotypic characterization of the strains on NYG agar plates revealed that inactivation of cepacian production (Δ rpfR Δ bceC , Δ rpfR Δ gtaB , and Δ rpfR Δ bceC Δ gtaB) did not abolish the wrinkled phenotype but led to flatter and smoother macrocolonies relative to the Δ rpfR mutant, suggesting that cepacian contributes to the architecture of microcolonies but is not the actual cause of wrinkle formation.…”
Section: Resultssupporting
confidence: 90%
“…2A , cepacian production was significantly reduced in the single mutants Δ bceC and Δ gtaB and completely abolished in the Δ bceC Δ gtaB double mutant, indicating that both cepacian clusters bce-I and bce-II are required for high-level cepacian production. Inactivation of rpfR had no apparent effect on cepacian production, suggesting that RpfR is not involved in the regulation of this EPS molecule, in agreement with a recent transcriptome analysis 21 . Phenotypic characterization of the strains on NYG agar plates revealed that inactivation of cepacian production (Δ rpfR Δ bceC , Δ rpfR Δ gtaB , and Δ rpfR Δ bceC Δ gtaB) did not abolish the wrinkled phenotype but led to flatter and smoother macrocolonies relative to the Δ rpfR mutant, suggesting that cepacian contributes to the architecture of microcolonies but is not the actual cause of wrinkle formation.…”
Section: Resultssupporting
confidence: 90%
“…S1A). Here, again, the prophage-mediated adaptation was not caused by the addition of new genes but rather by the disruption of an existing regulatory gene, which is a common initial route to increased fitness in new environments ( 38 40 ). Furthermore, competition between strains in chronic wounds can generate eco-evolutionary dynamics, where induced prophage can not only infect and kill susceptible competitors and favor resistant types but also produce new genotypes that are adapted to the phage-laden environment.…”
Section: Resultsmentioning
confidence: 97%
“…Since the first report introducing the bead-based experiment evolution setup 25 , which primarily focused on the ecological mechanisms that sustained biofilm diversity, numerous follow-up studies have validated the robustness of this model by describing the mutational patterns 59 , genetic properties 53 , 60 63 , niche complementarity 64 , 65 , and antibiotic resistance 66 , 67 . Unlike other laboratory-based experimental evolution systems, this simple method is useful for modeling the complex biofilm cycle, including initial attachment, biofilm maturation, dispersal, and recolonization 68 , 69 .…”
Section: Discussionmentioning
confidence: 99%